Microstructure And Electrical Study Of Biopolymer Based On Methylcellulose For Solar Cells - M.S. Nurhaziqah, A.; Q. Afiqah, I.; A. Nik Aziz, N.; Hasiah, S. (International Journal of Engineering and Technology, 2018)
The purpose of this research is to study effect of the addition of a various wt% of manganese chloride (MnCl2) salt on the methylcellulose (MC) biopolymer electrolyte.  The biopolymer electrolytes were prepared by using casting technique.  It is also thoroughly characterized of microstructure and electrical properties of the samples by using Fourier transform-infrared (FTIR) spectroscopy, X-ray Diffraction (XRD), Electrical Impedance Spectroscopy (EIS) and Linear Sweep Voltammetry (LSV).  Besides, the highest conductivity is sample MC:20wt%MnCl2 with value 0.74X10-6 Scm-1 measured by EIS.  The sample also achieved the excellent power conversion efficiency which is 0.31%.  It is augmented from the microstructure properties which are proved that the enhancement of the conductivity depends on the increment of the amorphous nature region and the complexation between MC and MnCl2 salt by XRD and FTIR
Keywords: Biopolymer; Methylcelluloce; Efficiency; FTIR; XRD